Microcystic serous cystadenoma mimicking pancreatic neuroendocrine neoplasm: report of a resected case with preoperative diagnostic difficulty and review of the literature - Shinichiro Nakamura; Yasuhiro Murata; Katsunori Uchida; Kenichiro Nishikawa; Yusuke Iizawa; Takehiro Fujii; Akihiro Tanemura; Naohisa Kuriyama; Masashi Kishiwada; Shugo Mizuno (Surgical Case Reports, 2022)
Abstract Background Microcystic pancreatic serous cystadenoma (SCA) can be managed without surgery in selected patients. However, the preoperative diagnosis of microcystic SCA remains challenging, and it is potentially misdiagnosed as other pancreatic cystic neoplasms or solid tumors, especially small microcystic SCA. Case presentation This was a case of a 27-year-old male patient with microcystic SCA causing difficulty in the differential diagnosis from pancreatic neuroendocrine neoplasm (pNEN). A pancreatic tail mass was incidentally discovered on abdominal ultrasound (US). A contrast-enhanced computed tomography (CT) scan revealed a solid tumor measuring 13 mm with early enhancement in the arterial phase at the pancreatic tail. The tumor showed low intensity on T1-weighted magnetic resonance image, high intensity on T2-weighted image, and a slightly hyperechoic mass on endoscopic US (EUS). EUS-fine needle aspiration (EUS-FNA) did not lead to a definitive diagnosis. The tumor was clinically diagnosed as a pNEN, and a laparoscopic spleen-preserving distal pancreatectomy using the Warshaw technique was performed. The final histopathological diagnosis was microcystic SCA. Conclusion Small microcystic SCA is difficult to distinguish from a hypervascular pancreatic tumor such as pNEN on imaging studies, and it is necessary to focus on the tumor echogenicity of EUS to differentiate microcystic SCA from pNEN preoperatively.